Tectonic Controls on Carbon and Serpentinite Storage in Subducted Upper Oceanic Lithosphere for the Past 320 Ma - Merdith, Andrew S.; Atkins, Suzanne E.; Tetley, Michael G. (Frontiers in Earth Science, 2019)
The subduction of upper oceanic lithosphere acts as a primary driver of Earth’s deep carbon and water cycles, providing a key transportation mechanism between surface systems and the deep Earth. Carbon and water are stored and transported in altered oceanic lithosphere. In this study, we present mass estimates of the subducted carbon and serpentinite flux from 320 to 0 Ma. Flux estimates are calculated using a full-plate tectonic reconstruction to build a descriptive model of oceanic lithosphere at points along mid-ocean ridges. These points then track the kinematic evolution of the lithosphere until subduction. To address uncertainties of modeled spreading rates in synthetic ocean basins, we consider the preserved recent (83–0 Ma) spreading history of the Pacific Ocean to be representative of the Panthalassa Ocean. This analysis suggests present-day subducting upper oceanic lithosphere contains 10–39 Mt/a of carbon and 900–3500 Mt/a of serpentinite (∼150–450 Mt/a of water). The highest rates of carbon delivery to trenches (20–100 Mt/a) occurred during the Early Cretaceous, as upper oceanic lithosphere subducted during this period formed in times of warm bottom water and the Cretaceous period experienced high seafloor production and consumption rates. Additionally, there are several episodes of high serpentinite delivery to trenches over the last 100 Ma, driven by extensive serpentinization of mantle peridotites exposed at slow spreading ridges. We propose variations in subduction regimes act as the principal control on the subduction of carbon stored in upper oceanic lithosphere, as since 320 Ma the volume of stored carbon across all ocean basins varies by less than an order of magnitude. For pre-Pangea times (<300 Ma), this suggests estimates of seafloor consumption represent a reasonable first-order approximation of carbon delivery. Serpentinite and associated water flux at subduction zones appear to be primarily controlled by the spreading regime at mid-ocean ridges. This is apparent during times of supercontinent breakup where slow spreading ridges produce highly serpentinized crust, and is observed in the present-day Atlantic, Arctic and Indian oceans, where our model suggests upper oceanic lithosphere is up to ∼100 times more enriched in serpentinite than the Panthalassa and Pacific oceans.